An Empirical Ascertainment of the Causes of Building Failure and Collapse in Nigeria - Ayedun, C. A.; Durodola, O. D.; Akinjare, O. A. (Mediterranean Journal of Social Sciences, 2012)
The incessant of building failure and collapse in the recent past has become a source of national concern andembarrassment in Nigeria. News reports of such incidents are frequently reported in the country by both the print and electronicmedia. In 2006 alone, no fewer than thirteen of such cases were recorded in Lagos State alone while statistics of the previousand subsequent years were not better off either. This study was set out to empirically ascertain the causes of such buildingfailure and collapse from the perspectives of the stakeholders (comprising of the professionals in the building industry,contractors and house owners/developers) with a view to proffering appropriate recommendations to guide against futureoccurrence. Lagos State was chosen as the case study based on the frequency of occurrence building collapse in the state. Toachieve the objective of the study, questionnaires were randomly administered on the professional Estate Surveyors andValuers, Architects, Town Planners, Quantity Surveyors, Engineers (Structural and Civil), building contractors andLandlords/developers in the study area to seek their opinion on their perceived causes of building collapse. The study identifiedthe use of sub-standard building materials, poor workmanship by contractors, use of incompetent contractors, faulty constructionmethodology, heavy downpour, non compliance with specifications/standards by developers/contractors, inadequate/lack ofsupervision/inspection/monitoring, structural defects, defective design/structure, illegal conversion/alterations/additions toexisting structures and dilapidating structures as the major causes of building collapse in Lagos State nay Nigeria. The studyrecommends education of all the stakeholders including the professionals in the building industry and landlords/developers onthe inherent dangers of building collapse and the need to be safety conscious while building houses.